The Effectiveness of Learning Style-Based Instructional Models in Javanese Language Learning - Arista Susiyanti; Joko Sukoyo; Endang Kurniati (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Low student engagement in learning indicates that the instructional process has not fully accommodated students’ diverse learning styles. This study aimed to analyze the effectiveness of a learning style-based instructional model in Javanese language learning at the senior high school level. The research employed an experimental method using a posttest only control group design. The participants were eleventh-grade students of SMA Negeri 16 Semarang selected through a cluster random sampling technique. The study involved two groups: class XI 6 as the experimental group receiving the learning style-based instructional model and class XI 5 as the control group receiving conventional instruction. The research instruments consisted of a learning achievement test and a learning style questionnaire. Data were analyzed using the non-parametric Mann–Whitney U test because the Shapiro–Wilk normality test indicated that the data were not normally distributed. The findings revealed a significant difference between the experimental and control groups with a p-value of 0.045 (<0.05). These findings indicate that the learning style-based instructional model is effective in Javanese language learning because it accommodates students’ diverse learning characteristics and enhances their engagement in the learning process.